Case Report: Use of Amniotic Microvesicles for Regenerative Medicine Treatment of a Mare With Chronic Endometritis - Lange-Consiglio, Anna; Funghi, Federico; Cantile, Carlo; Idda, Antonella; Cremonesi, Fausto; Riccaboni, Pietro (Frontiers in Veterinary Science, 2020)
Chronic endometritis is an inflammation in the inner layer of uterine mucosa, with or without an infectious process, which affects the animal’s fertility but not its general health. A variety of treatments has been adopted over the years but to date no effective cures have been able to renew the injured tissue. Since the defects in the foetal maternal communication are caused by degenerative changes due to chronic endometrial inflammation, our working hypothesis was a new approach to this disease by the regenerative medicine using amniotic derived microvesicles (MVs) for their anti-inflammatory and regenerative effects. The MVs are responsible for horizontal transfer of genetic materials, including microRNA (miRNAs) that are involved in paracrine communication between origin cells and target cells. Thus, intrauterine MV infusion may be beneficial in degenerative chronic endometritis and in the foetal-maternal talk. The selected mare was an 11-year-old Friesian, with a history of failed pregnancies despite numerous insemination attempts. Punctual and evident heats characterized the reproductive history, but no insemination attempts had been made for many years. The first (failed) insemination was when the mare was 9-years-old. In the next two reproductive seasons, other attempts were made at regular intervals but none was successful. After a final insemination attempt using a stallion of proven fertility, the collection of an 8-day old embryo confirmed that the mare was affected by implantation failure related to endometritis. The mare was treated with two cycles of intrauterine administration of amniotic-derived MVs. The success of the intrauterine administration of MVs was demonstrated by an improvement in the classification of endometritis and in a successful artificial insemination (AI) with implantation of an embryo, as detected at day 14. Probably, MVs were able to restore the injured endometrium and re-establish the proper communication for a successful embryo implantation.